Circulating inflammatory markers in cervical cancer patients and healthy controls. Issue 1 (1st January 2020) - Vitkauskaite, Agne; Urboniene, Daiva; Celiesiute, Joana; Jariene, Kristina; Skrodeniene, Erika; Nadisauskiene, Ruta Jolanta; Vaitkiene, Daiva
Abstract: There is increasing evidence that host inflammatory responses play an important role in the development and progression of cancers. There are some data that cancer is associated not only with inflammation at the site of the lesion, but also with dysregulations of the host overall systemic immune response. In the case of cervical cancer, inflammation is an important factor associated with the development, progression, and potential metastasis of the disease. What is unclear still in the potential for modifications of host responses to human papillomaviruses (HPV) – a known causative agent of CC, that could be induced by cigarette smoking. In particular, it remains to be determined how the inflammation induced by HPV infection could impact on CC incidence/severity. In this prospective study, serum levels of 10 cytokines were evaluated using Multiplex and ELISA assays. The samples were the sera of 43 CC patients and 60 healthy (NILM) controls. All outcomes were evaluated in relation to host HPV and to their smoking status. The results in indicated that serum sTREM-1, TNFα, IFNβ, IL-1β, and IL-6 levels were significantly increased in CC (HPV+) patients compared to healthy NILM controls. A similar trend was observed for IL-10 and IL-2 levels. Within the two groups, differences in cytokine levels between smokers and never smokers were not remarkable. The findings here support the hypothesized role of systemic inflammation in the pathophysiology of CC.